The Impacts of Students Association on The Students' Academic Achievement - Nur Malikul Mulki Rahman; Sukardi Weda; Maemuna Muhayyang (PT ARRUS Intelektual Indonesia, 2024)
This mixed-methods research aims to investigate the impact of student associations on students' academic achievement. A scale test administered by a questionnaire using Likert scale was used to collect data. The distribution of questionnaires was addressed to the administrator of HMPS ACCESS for the 2023-2024 period to determine the impact of student association on their academic achievement; the score of student academic achievement was taken from student GPA. 39 students from the HMPS ACCESS board were purposely taken as the sample as they are active members of the student association in the English Education Study Program. It was found that the student association (X) impacted the students’ academic achievement (Y) indicated by the mean score of the questionnaire which is 42.2 falling into the impacted category. This finding takes into account that the student associations can positively contribute to the students’ academic achievement as long as they utilize and place both proportionally.